Metagenomic Analysis of a Biphenyl-Degrading Soil Bacterial Consortium Reveals the Metabolic Roles of Specific Populations - Garrido-Sanz, Daniel; Manzano, Javier; Martín, Marta; Redondo-Nieto, Miguel; Rivilla, Rafael (Frontiers in Microbiology, 2018)
Polychlorinated biphenyls (PCBs) are widespread persistent pollutants that cause several adverse health effects. Aerobic bioremediation of PCBs involves the activity of either one bacterial species or a microbial consortium. Using multiple species will enhance the range of PCB congeners co-metabolized since different PCB-degrading microorganisms exhibit different substrate specificity. We have isolated a bacterial consortium by successive enrichment culture using biphenyl (analogue of PCBs) as the sole carbon and energy source. This consortium is able to grow on biphenyl, benzoate and protocatechuate. Whole-community DNA extracted from the consortium was used to analyze biodiversity by Illumina sequencing of a 16S rRNA gene amplicon library and to determine the metagenome by whole-genome shotgun Illumina sequencing. Biodiversity analysis shows that the consortium consists of 24 OTUs (≥ 97% identity). The consortium is dominated by strains belonging to the genus Pseudomonas, but also contains betaproteobacteria and Rhodococcus strains. WGS analysis resulted in contigs containing 78.3 Mbp of sequenced DNA, representing around 65% of the expected DNA in the consortium. Bioinformatic analysis of this metagenome has identified the genes encoding the enzymes implicated in three pathways for the conversion of biphenyl to benzoate and five pathways from benzoate to TCA cycle intermediates, allowing us to model the whole biodegradation network. By genus assignment of coding sequences, we have also been able to determine that the three biphenyl to benzoate pathways are carried out by Rhodococcus strains. In turn, strains belonging to Pseudomonas and Bordetella are the main responsible of three of the benzoate to TCA pathways while the benzoate conversion into TCA cycle intermediates via benzoyl-CoA and the catechol meta cleavage pathways are carried out by beta proteobacteria belonging to genera such as Achromobacter and Variovorax. We have isolated a Rhodococcus strain WAY2 from the consortium which contain the genes encoding the three biphenyl to benzoate pathways indicating that this strain is responsible for all the biphenyl to benzoate transformations. The presented results show that metagenomic analysis of consortia allows the identification of bacteria active in biodegradation processes and the assignment of specific reactions and pathways to specific bacterial groups.